CAUSES OF POISONING AND MEASURES TO PREVENT IT (Conference Zone, 2022)
Any foreign substance that enters the body and causes poisoning, illness or death is a poison. The consequences of poisoning depend on the type and quantity of the poisonous substance, the time of the poisoning, how long the contact with the poisonous substance lasted, the physiological parameters of the victim (age, weight) and the way it entered the body.